Preliminary Development of Abrader Tool for Paper De-Printing Apparatus using Taguchi Method - Masni-Azian, Akiah; Toibah, Abd Rahim; Mohd Nazrin, Muhammad; Zuraida, Abdul Majid (2012)
Removing toner/print from paper is identified as one of the solution towards paper recycling. Instead of opting for conventional paper recycling method by pulping the solid structure to form a new moulded pulp, another way towards paper recycling is by removing the print/toner on paper so that the paper can be used again before it fracture. This paper describes the preliminary development of a customized abrader tool for paper de-printing apparatus using abrasion mechanism. The control system for the apparatus has been modified from an existing printer. Parameters studied include abrading load, abrader shape and number of passes. Optimum parameter selection is determined by using Taguchi method.